2011
DOI: 10.1074/jbc.m111.265942
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Type 3 Effector Nodulation Outer Protein L (NopL) from Rhizobium sp. NGR234

Abstract: Rhizobia are nitrogen-fixing bacteria that induce nodules on roots of legume host plants. Nodule initiation is triggered by rhizobial Nod factors, i.e. lipo-chitooligosaccharidic nodulation signals produced in response to host flavonoids in the rhizosphere (1). Additional symbiotic determinants produced by specific rhizobial strains often influence establishment of symbiosis in a host-specific manner. For example, rhizobial effector proteins secreted by bacterial secretion systems can significantly affect nodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…Rhizobial T3E genes show genetic patterns indicative of surprising conservation, pointedly contrasting the patterns consistent with the dynamic arms race model of co-evolution dogmatic for T3Es (Figures 3–5). This finding is particularly striking in light of the observations that T3Es of mutualistic rhizobia are similar in regards to those of pathogens in having to maintain sufficiency in engaging and dampening PTI while avoiding ETI [15], [17], [24], [47]. Moreover, we demonstrated that the high conservation of T3Es in rhizobia relative to phytopathogens is not likely driven by differences in host range or phylogenetic diversity among genomes (Figures 1, S2, 4, and 5).…”
Section: Resultssupporting
confidence: 54%
“…Rhizobial T3E genes show genetic patterns indicative of surprising conservation, pointedly contrasting the patterns consistent with the dynamic arms race model of co-evolution dogmatic for T3Es (Figures 3–5). This finding is particularly striking in light of the observations that T3Es of mutualistic rhizobia are similar in regards to those of pathogens in having to maintain sufficiency in engaging and dampening PTI while avoiding ETI [15], [17], [24], [47]. Moreover, we demonstrated that the high conservation of T3Es in rhizobia relative to phytopathogens is not likely driven by differences in host range or phylogenetic diversity among genomes (Figures 1, S2, 4, and 5).…”
Section: Resultssupporting
confidence: 54%
“…Simultaneous analysis of two or more proteins in the same plant cell has gained increasing importance. Examples include work on a bacterial type-3 secretion effector (Zhang et al 2011), targeted transgene integration into plant cells (Cai et al 2009), and subcellular localization of proteins (Marion et al 2008). As this approach requires transformation of the same host cell by two bacteria, optimal transformation conditions must be chosen and the percentage of co-transformed cells should be as high as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Transformation of tobacco leaves is also widely used to study the function of microbial effectors delivered into plant cells (e.g. Dai et al 2008;Krasileva et al 2010;Zhang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, besides secretion and translocation into host cells, only a few rhizobial T3 effectors have been biochemically characterized in detail. Examples of well-studied rhizobial effectors are the nodulation outer proteins NopE1/NopE2 (Wenzel et al, 2010;Schirrmeister et al, 2011), NopL (Bartsev et al, 2003;Bartsev et al, 2004;Zhang et al, 2011;Ge et al, 2016), NopM (Rodrigues et al, 2007;Kambara et al, 2009;Xin et al, 2012;Xu et al, 2018), NopP (Ausmees et al, 2004;Skorpil et al, 2005;Zhao et al, 2018;Sugawara et al, 2018), NopT (Dai et al, 2008;Dowen et al, 2009;Kambara et al, 2009;Fotiadis et al, 2012), and ErnA (Teulet et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The T3 effector NopL of Sinorhizobium sp. (=Ensifer fredii) NGR234, for example, becomes multiply phosphorylated by MAP kinases and thereby inhibits MAP kinase signaling (Zhang et al, 2011;Ge et al, 2016). On the other hand, plants can recognize the presence or action of a specific T3 effector (avirulence protein) by a given intracellular disease resistance protein (nucleotidebinding/leucine-rich repeat receptor).…”
Section: Introductionmentioning
confidence: 99%